Performance Evaluation of some SDN Controllers Towards Scalable and Distributed SDN - احمد احمد; ديب حازم (Latakia University Journal -Engineering Sciences Series, 2021)
Software-Defined Networking (SDN) is an emerging network architecture that is adaptable, dynamic, cost-effective, and manageable. The SDN architecture is a form of network virtualization where the network controlling and forwarding functions are separated. This research mainly focuses on three controllers, POX, a Python based controller, Mul, a C based controller, and OpenDayLight, a Java based controller. A performance comparison of these controllers is effected over four different SDN network topologies which are: single, linear, tree and a fourth proposed topology. The performance evaluation has been processed by measuring two factors which are: Throughput and Round Trip Time. The performance comparison has been done using the network simulator Mininet. The results show that the OpenDayLight controller gives better performance than both POX controller in all different topologies, and better than MUL in three of the four tested topologies, and that was according to the two factors in the different environments which were studied.